Prevention of Post-Transfusion Hepatitis by Screening of Antibody to Hepatitis B Core Antigen in Healthy Blood Donors - Shastry, S. (Università Cattolica del Sacro Cuore, 2011)
BACKGROUND: Transfusion-associated hepatitis B viral infection continues to be a major problem in India even after adoption of mandatory screening for HBsAg by ELISA method. The high incidence of TAHBV is reported in patients receiving multiple transfusions. OBJECTIVE: To study the seroprevalence of hepatitis B core antibody among healthy voluntary blood donors SUBJECTS AND METHODS: The study was conducted in the department of Transfusion Medicine of a tertiary care referral hospital. A total of 12,232 volunteers after passing through the stringent criteria were selected for blood donation. Donor samples were tested for all mandatory transfusion transmissible infections and anti HBc IgM (Monolisa HBc IgM PLUS:BIO-RAD, France). Reactive results were confirmed by repeat testing in duplicate. Donor data was analyzed using SPSS software and Chi-square test was used to calculate the significance of difference between the groups. RESULTS: A total of 12,232 healthy voluntary blood donors were recruited. Majority (93.4%) were males. Median age of donor population was 26 years (range: 18–60 years). Eighty six (0.7%) were positive for HBsAg, which comes under “low prevalence (<2%) zone” as per WHO. On screening for HBcAg Ig M, 15 (0.1%) were found to be positive and none were HBsAg reactive. There was no significance of difference in the mean age between reactive and non-reactive donors. CONCLUSION: Evaluating the usefulness of anti-HBc screening is critical. Anti HBcAg IgM screening may be included in routine screening of donors as it is an indicator of occult HBV during window period. The cost and the unnecessary wastage of the blood units when they are positive for anti HBsAg along with the core antibody need to be studied.